2021
DOI: 10.3390/antiox10020218
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Nicotinamide Adenine Dinucleotide Phosphate (NADPH) Oxidase and Its Inhibitors in Alzheimer’s Disease Murine Models

Abstract: Alzheimer’s disease (AD) is one of the main human dementias around the world which is constantly increasing every year due to several factors (age, genetics, environment, etc.) and there are no prevention or treatment options to cure it. AD is characterized by memory loss associated with oxidative stress (OS) in brain cells (neurons, astrocytes, microglia, etc.). OS can be produced by amyloid beta (Aβ) protein aggregation and its interaction with metals, mitochondrial damage and alterations between antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 153 publications
(100 reference statements)
0
12
0
Order By: Relevance
“…In addition, LPS is one of the potent factors capable of activating NOX2 in the CNS [ 164 , 175 ]. The NOX2 activation in glia and neurons can induce neuronal cell death through massive oxidative stress, which has been suggested as a contributor to several neurodegenerative diseases, including AD [ 176 , 177 ]. The LPS-induced neuroinflammation such as NOX2 activation can be a possible additional contributor to neurodegeneration in AD pathology.…”
Section: Specific Roles Of Lps From Gram-negative Bacteria In Admentioning
confidence: 99%
“…In addition, LPS is one of the potent factors capable of activating NOX2 in the CNS [ 164 , 175 ]. The NOX2 activation in glia and neurons can induce neuronal cell death through massive oxidative stress, which has been suggested as a contributor to several neurodegenerative diseases, including AD [ 176 , 177 ]. The LPS-induced neuroinflammation such as NOX2 activation can be a possible additional contributor to neurodegeneration in AD pathology.…”
Section: Specific Roles Of Lps From Gram-negative Bacteria In Admentioning
confidence: 99%
“…This may have important pathological implications, as oxidative damage to these structures as a result of increased Nox 2 activity could disrupt normal central control of the micturition reflex and cause voiding disorders. Indeed, in several other chronic brain disorders, Nox 2 has been suggested to contribute to inflammation and oxidative damage [ 14 , 15 , 17 ]. This warrants further investigation into the role of Nox 2 in these brain regions in neurogenic bladder dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst Nox 4 is the first recognized Nox subtype in the CNS, and mainly participates in cell signalling but may also be involved in stroke, Nox 2 has been shown to mainly contribute to pathological damage [ 15 , 16 ]. The importance of Nox and associated ROS overproduction is evidenced by increased expression of Nox subtypes in experimental CNS damage and in certain pathological samples [ 14 , 15 , 17 ] and by the protective effect of interventions with small-molecule Nox inhibitors and Nox knockout [ 13 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. However, further progress in understanding the pathological basis of Nox-derived ROS in brain damage requires knowledge of the specific distribution of Nox subtypes and associated ROS production in specialized brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported no changes in 3HK levels in AD patients compared to controls, in either central or peripheral levels (Baran, Jellinger et al 1999, Gulaj, Pawlak et al 2010, Jacobs, Lim et al 2019, Sorgdrager, Vermeiren et al 2019). KMO enzyme requires NADPH as a coenzyme (Hughes, Guner et al 2022) and, therefore, the overactivity of NADPH oxidase enzyme consumes NADPH in AD patients (Fragoso-Morales, Correa-Basurto et al 2021), which may cause attenuated KMO enzyme activity.…”
Section: Discussionmentioning
confidence: 99%